PERLINDUNGAN HUKUM BAGI WISATAWAN PADA OBJEK WISATA TIRTA ARUNG JERAM SUNGAI AYUNG DI KABUPATEN GIANYAR - Ida Bagus Indra Brahmana; Putu Lantika Oka Permadhi (Jurnal Hukum Mahasiswa, 2023)
The scope of this research is on rafting attractions by focusing the research subject on tourists who use rafting tourism services, and the location is in PT. Tear Bali. The formulation of research problems is related to legal protection for tourists in tirta rafting attractions and about the responsibility of Ayung River rafting business actors in Gianyari Regency to face losses experienced by tourists. The results of the analysis show that legal protection for users of Tirta Arung Jeram Sungai Ayung services in Gianyar Regency at PT Bali Sobek Utama has been realized. This is evidenced by the good faith of PT. Sobek Bali Utama which carries out its business activities by realizing protection in the form of providing insurance to consumers / tourists who have been covered or included in tour packages provided in accordance with applicable law. In addition, the responsibility of rafting business actors at PT Sobek Bali Utama has been carried out properly in accordance with the provisions of the Law regulated in article 26 letter d, e and letter n in Law Number 10 of 2009 concerning Tourism.